2006
DOI: 10.1021/bi0620095
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Mechanism of Tryptophan 2,3-Dioxygenase, a Heme Enzyme Involved in Tryptophan Catabolism and in Quinolinate Biosynthesis,

Abstract: The structure of tryptophan 2,3-dioxygenase (TDO) from Ralstonia metallidurans was determined at 2.4 A. TDO catalyzes the irreversible oxidation of l-tryptophan to N-formyl kynurenine, which is the initial step in tryptophan catabolism. TDO is a heme-containing enzyme and is highly specific for its substrate l-tryptophan. The structure is a tetramer with a heme cofactor bound at each active site. The monomeric fold, as well as the heme binding site, is similar to that of the large domain of indoleamine 2,3-dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
133
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(144 citation statements)
references
References 30 publications
10
133
1
Order By: Relevance
“…Expression and Purification of Ferric TDO-The construction of the plasmid encoding full-length Cupriavidus metallidurans TDO (CmTDO) has been described elsewhere (13). The protein was purified by using a 100-ml HiLoad nickel-affinity column and a Superdex 200 size-exclusion column on an Ä KTA FPLC system as described in an earlier spectroscopic study of the enzyme (24).…”
Section: Reagents-l-trpmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression and Purification of Ferric TDO-The construction of the plasmid encoding full-length Cupriavidus metallidurans TDO (CmTDO) has been described elsewhere (13). The protein was purified by using a 100-ml HiLoad nickel-affinity column and a Superdex 200 size-exclusion column on an Ä KTA FPLC system as described in an earlier spectroscopic study of the enzyme (24).…”
Section: Reagents-l-trpmentioning
confidence: 99%
“…TDO is a homotetramer with a total mass of ϳ134 kDa, whereas IDO is a monomeric protein. The two enzymes share only 14% sequence identity but conserve similar active site architectures (11)(12)(13). In addition to humans, TDO has also been found in other mammals, such as rats and mice, as well as in mosquitoes and bacteria (2, 5, 14 -18).…”
mentioning
confidence: 99%
“…The 3-indolenylperoxy intermediate subsequently converts to the product, NFK, via either a Criegee rearrangement or a dioxetane pathway. A major breakthrough in the understanding of the heme-based dioxygenase chemistry was made recently by the unveiling of the crystallographic structures of hIDO and 2 bacterial isoforms of TDO (23)(24)(25). Structure-based sequence alignment shows that the proximal histidine ligand and most of the critical distal residues involved in substrate-protein interactions in TDO are conserved in IDO (24,25).…”
mentioning
confidence: 99%
“…A major breakthrough in the understanding of the heme-based dioxygenase chemistry was made recently by the unveiling of the crystallographic structures of hIDO and 2 bacterial isoforms of TDO (23)(24)(25). Structure-based sequence alignment shows that the proximal histidine ligand and most of the critical distal residues involved in substrate-protein interactions in TDO are conserved in IDO (24,25). Spectroscopic studies suggested that the active site base for hTDO is an evolutionarily conserved residue, H76, while that in hIDO is the heme-bound dioxygen (see SI Text and Fig.…”
mentioning
confidence: 99%
“…Apart from covering the top of the heme-binding site, the role of the noncatalytic small domain is unclear. Interestingly, TDO has a homotetrameric structure, in which each monomer, when aligned to IDO, appears to contain the large catalytic but not the small domain (31). Although not crystallized yet, the protein sequence of IDO2 suggests that it also possesses the small domain (29).…”
Section: Idos Itims and Evolutionmentioning
confidence: 99%